2014
DOI: 10.1080/09658211.2014.912331
|View full text |Cite
|
Sign up to set email alerts
|

Memory and comprehension for health information among older adults: Distinguishing the effects of domain-general and domain-specific knowledge

Abstract: While there is evidence that knowledge influences understanding of health information, less is known about the processing mechanisms underlying this effect and its impact on memory. We used the moving window paradigm to examine how older adults varying in domain-general crystallized ability (verbal ability) and health knowledge allocate attention to understand health and domain-general texts. Participants (n=107, aged 60 to 88 yrs) read and recalled single sentences about hypertension and about non-health topi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 36 publications
4
29
0
Order By: Relevance
“…This is not only of theoretical import in defining the cognitive architecture of language processing across the lifespan (e.g., Just and Carpenter, 1992 ; Stine-Morrow and Payne, 2016 ), but also suggests applications for improving cognitive functioning among older adults in significant ways ( Stine-Morrow and Basak, 2011 ). Because age-related declines in language comprehension and memory can have far-reaching effects as adults navigate the ordinary demands of work, family, and health (e.g., Morrow et al, 2006 ; Chin et al, 2015 ), the development of pathways to mitigate such deficits offers promise for promoting late-life well-being.…”
Section: Discussionmentioning
confidence: 99%
“…This is not only of theoretical import in defining the cognitive architecture of language processing across the lifespan (e.g., Just and Carpenter, 1992 ; Stine-Morrow and Payne, 2016 ), but also suggests applications for improving cognitive functioning among older adults in significant ways ( Stine-Morrow and Basak, 2011 ). Because age-related declines in language comprehension and memory can have far-reaching effects as adults navigate the ordinary demands of work, family, and health (e.g., Morrow et al, 2006 ; Chin et al, 2015 ), the development of pathways to mitigate such deficits offers promise for promoting late-life well-being.…”
Section: Discussionmentioning
confidence: 99%
“…General knowledge (i.e., linguistic/verbal knowledge, or crystallized ability) and domain-specific knowledge, on the other hand, often support comprehension processes. More knowledgeable readers recognize words more quickly and are better able to integrate the associated concepts into the textbase (Chin et al, 2015;Payne, Gao, Noh, Anderson, & Stine-Morrow, 2012). Although processing capacity declines with age, knowledge tends to increase or remain invariant (Horn & Cattell, 1967;Li et al, 2004), depending on literacy (Stanovich, West, & Harrison, 1995) and domain-specific (Beier & Ackerman, 2005;Chin et al, 2009) experience.…”
mentioning
confidence: 99%
“…The P-K model also focuses on the potential of knowledge to offset age-related processing capacity limits in order to support health literacy, decisions, and behaviors. Knowledge improves performance on the REALM and STOFHLA tests (Chin et al, 2011) as well as comprehension of health information (Chin et al, 2015;Miller, Stine-Morrow, Kirkorian, & Conroy, 2004). Wolf and colleagues (2012) found that measures of general knowledge, as measured by vocabulary, partially contributed to the impact of health literacy on understanding and remembering health information.…”
mentioning
confidence: 99%
“…To be able to act as an active agent in healthcare, people also need to be able to understand and act on health information (see e.g. Chin et al, 2015). Those who have higher levels of both health literacy (HL), that is, the ability to obtain, understand, and use health information (e.g.…”
Section: Ageing and Access To Health Informationmentioning
confidence: 99%
“…Inadequate health literacy and health information literacy can therefore be barriers to engagement (see e.g. Chin et al, 2015).…”
Section: Ageing and Access To Health Informationmentioning
confidence: 99%